Fetal Heart Rate Variability due to Vibroacoustic Stimulation: Linear and Nonlinear Contribution - Magenes, G.; Signorini, M. G.; Arduini, D.; Cerutti, S. (Methods of Information in Medicine, 2004)
Objectives: This work aims at characterizing the variation of fetal heart rate (FHR) provoked by vibro-acoustic stimulation (VAS). The FHR signal is analyzed by means of a multiparametric approach consisting of linear and nonlinear indices.Methods: The FHR signals of 13 fetuses were collected through a US standard CTG monitor (HP1351A) and were sampled at a frequency of 2 Hz. The VAS was provided after a period of quiet of 10 minutes. The analysis was performed on the quiet period and on two successive time windows of 10 minutes each, after the stimulation. FHR classical parameters (delta, short term variability, long term irregularity, accelerations and decelerations) as well as power spectral density (PSD) and approximate entropy (ApEn) were computed for each period.Results: Results confirm that there is a significant change in fetal conditions after the stimulus is applied. This change can be clearly observed either in time domain parameters and in the regularity index (ApEn). Individual data are all consistent with an increase of variability and a decrease of regularity after VAS.Conclusions: The obtained results give further strength to the hypothesis that vibratory stimuli tests represent a reliable method for monitoring the neural development of the fetus during pregnancy.
Keywords: Fetal heart rate; vibroacoustic stimulation; multipara-metric analysis